The production without pesticides in the control of oat foliar diseases: resistance inducer by silicon and potassium and escape zone (Research, Society and Development, 2022)
White oat is a winter species with numerous benefits to cultivation systems and animal and human nutrition. It is recognized as a nutraceutical food for its health benefits. This condition has promoted the increase of cultivation areas seeking to meet the demand, however, favoring the emergence of fungal diseases, responsible for expressive damages in the productivity and quality of grains. Leaf rust (Puccinia coronata f. sp avenae) and helminthosporiose (Drechslera avenae (Eidam) Sarif) are the most relevant due to their aggressiveness. These diseases are not satisfactorily controlled by genetic resistance and their occurrence and aggressiveness is related to the presence of a favorable environment for the development of fungi, a susceptible host, and a virulent pathogen. The use of fungicide has been the most efficient alternative of control, in the guarantee of productivity with economic return to the farmer. However, the use of pesticides has generated discussions about the adverse effects on the environment, food safety and public health, a condition that reinforces the search for more sustainable agricultural systems. This review seeks to present a deep discussion about pesticides and more sustainable alternatives that can reduce and/or avoid the incidence and severity of fungal diseases in oats. Among the alternatives, the discussion encompasses two potential management technologies, sowing involving escape zones to restrict the development of fungi and the use of abiotic resistance inducers by silicon and potassium.